Mapping student learning motivation research trends (2000–2024): a bibliometric analysis advancing SDG 4 and SDG 10 in education - Fauzee, Mohd Sofian Omar; Al-Zu’bi, Mohammad Ahmad Abdelaziz; Al-Mseidin, Kholoud Imhammad Meqbel; Singh, Daljit Singh Gurbaksh; Habibie, Akhmad; Al-Mawadieh, Reda S.M.; Mahmood, Waqas; Fatimah Noor Rashidah, M. S.; Abdullah, Muhammad Nazrul Hakim; Mohd Yaakob, Mohd Faiz (Eurasian Society of Educational Research, 2026)
This bibliometric review maps two decades of Scopus-indexed literature (2000–2024) to analyze the evolving landscape of student learning motivation and identify emerging thematic dimensions. Using Harzing’s Publish or Perish, VOSviewer, and Microsoft Excel, a total of 560 publications were extracted, filtered, and analyzed. Keyword co-occurrence and content analysis were employed to generate thematic clusters and synthesize conceptual dimensions. Findings reveal a steady growth of literature from 2000, with citations peaking in 2013 and again in 2019, reflecting an increased interest in motivational constructs integrated with educational technologies. The ACM International Conference Proceeding Series led in volume of publications, while highly cited articles focused on gamification, augmented reality, mobile learning, and artificial intelligence. From 70 co-occurring keywords, six clusters emerged: (1) Motivated Learning Strategies, (2) Digital Learning Experience and Cognitive Response, (3) Interactive and Language-Based Pedagogy, (4) Teaching Quality and Instructional Depth, (5) Curriculum Innovation and Student-Centered Technology, and (6) Collaborative and Active Learning. These clusters collectively define the overarching framework of Learner-Centered Education in Technology-Enhanced Environments. This study contributes a novel classification of research clusters into coherent, actionable dimensions, offering researchers, educators, and policymakers a thematic roadmap to address gaps and future directions. It highlights the theoretical integration of self-determination, ARCS, and flow theory with emerging pedagogical tools. The findings promote inclusive, adaptable, and technology-enabled learning strategies critical for motivating diverse learners in the 21st century, aligning with SDG 4: Quality Education and SDG 10: Reduced Inequalities. Recommendations are proposed to expand bibliometric coverage, integrate qualitative insights, and support equitable education policy development.